2020
DOI: 10.5812/pedinfect.94416
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of Chikungunya and West Nile Viruses in Iranian Children in 2018

Abstract: Background: Several surveys have been conducted on the seroprevalence of viral infections caused by Chikungunya and West Nile viruses in humans. However, there is a paucity of studies on the seroprevalence and spread of these viruses in children. Objectives: We aimed to investigate the seropositivity of IgG antibodies against Chikungunya and West Nile viruses in a group of Iranian children aged one month to 14 years. Methods: A cross-sectional study was performed on blood samples collected from children aged o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…A similar study by Tavakoli et al, 2020, examined serum from patients from 7 different provinces (Khuzestan, Fars, Kerman, Ilam, Hormozgan, Bushehr, Sistan and Baluchestan) with 16.07% of the samples testing positive for CHIKV [15]. Another study in 2018 examining blood samples collected from children at a children's hospital in Tehran identified 2.2% positivity rate for CHIKV [47]. Similarly, serum samples collected in six provinces (Bushehr, Hormozgan, Sistan and Baluchestan, Khuzestan, Gilan and Mazandaran) from 2017 to 2018 revealed that 1.8% of the samples tested positive for CHIKV [48].…”
Section: Chikungunya Virus Situation In Iranmentioning
confidence: 95%
See 2 more Smart Citations
“…A similar study by Tavakoli et al, 2020, examined serum from patients from 7 different provinces (Khuzestan, Fars, Kerman, Ilam, Hormozgan, Bushehr, Sistan and Baluchestan) with 16.07% of the samples testing positive for CHIKV [15]. Another study in 2018 examining blood samples collected from children at a children's hospital in Tehran identified 2.2% positivity rate for CHIKV [47]. Similarly, serum samples collected in six provinces (Bushehr, Hormozgan, Sistan and Baluchestan, Khuzestan, Gilan and Mazandaran) from 2017 to 2018 revealed that 1.8% of the samples tested positive for CHIKV [48].…”
Section: Chikungunya Virus Situation In Iranmentioning
confidence: 95%
“…More studies examining ZIKV vectors need to be undertaken to elucidate the potential of disease spread in Iran, especially considering the presence of a main vector for the disease. [15,[46][47][48], Dengue virus [15,48,58,60,62], Sindbis virus [75] and Rift valley fever virus [109] in Iran in either humans, animals, or mosquitoes by indirect and direct evidence.…”
Section: Zika Virus Situation In Iranmentioning
confidence: 99%
See 1 more Smart Citation